ChemInform Abstract: Rhodium‐Catalyzed [5 + 2] Cycloaddition of 3‐Acyloxy‐1, 4‐enyne with Alkene or Allene. Issue 43 (7th October 2016) - Song, Wangze; Lynch, John C.; Shu, Xing‐zhong; Tang, Weiping
Abstract: Two novel types of [5 + 2] cycloaddition of 3‐acyloxy‐1, 4‐enyne with a tethered alkene or a tethered allene are developed.